ASSESSMENT OF THE RESULTS OF REVISION HIP AND KNEE REPLACEMENT SURGERY IN CASE OF PERIPROSTHETIC INFECTION - Kameka, Alexey L.; Grishchuk, Alexey N.; Leonova, Svetlana N. (Bajkalʹskij medicinskij žurnal, 2024)
Background. Periprosthetic infection is a serious complication of large joint replacement surgery. To date, there is no consensus on the choice of surgical tactics for treating this category of patients. The aim of the work. To determine the effectiveness of one-stage and two-stage revision hip and knee replacement surgery in reducing periprosthetic infection. Materials and methods. We analyzed the results of revision replacement surgery in 78 patients with deep periprosthetic infection of the hip and knee joints. In 38 patients, one-stage revision replacement surgery was used, in 40 patients – two-stage. Treatment results were assessed 1 year after the surgery. Out of 78 patients, in 45 (57.7 %) choosing the type of revision replacement surgery was made according to the algorithm developed at the Irkutsk Scientific Centre of Surgery and Traumatology. Results. Using revision replacement surgery made it possible to stop the infectious process in 64.1 % of patients. The best results were obtained after two-stage revision surgery, in which relief of the infectious process was achieved in 72.5 % of cases. The choice of treatment tactics for patients according to the algorithm improved the results of two-stage revision joint replacement surgery up to 87.5 %. Using the criteria proposed in the algorithm when assessing the positive and negative results of revision surgery made it possible to confirm the effectiveness of the algorithm in 80% of patients and to identify the probable reasons for the maintenance of periprosthetic infection: incorrect choice of the type of surgery, the presence of extensive bone defects, the presence of polyallergy. Conclusion. Analysis of the results of revision arthroplasty for periprosthetic infection made it possible to confirm the effectiveness of the proposed algorithm for choosing the type of surgery, to establish the highest effectiveness of two-stage revision surgery compared to one-stage surgery, and also to determine the probable causes of negative treatment results.